Sustainability and carbon footprint evaluation at university: case study of VILNIUS TECH - Garnevičius, Mantas; Šerevičienė, Vaida; Grubliauskas, Raimondas; Mikučionienė, Rūta (Technological and Economic Development of Economy, 2025)
Because of a societal push towards sustainability a problem emerges of adapting the concept to different sectors of the economy and society. The differing complexities of different fields and social structures make it difficult to create a universal sustainability strategy. Higher education institutions (HEIs) consist of a broad range of people, working in various fields of industry, making it an appropriate cross-section of the nation. Adapting sustainability practices in these institutions would allow to screen for successful policies before implementing them more widely, detecting most effective practices, allowing a faster transition towards achieving the Sustainable Development Goals (SDGs). It is hard to decide where to start, as many sustainable practices exist. This article presents the case study of VILNIUS TECH and conducts a comparison with universities in the region, determining best sustainability practices. The Greenhouse gas (GHG) protocol standard was used to form the emission inventory. The university comparison will help identify effective HEIs carbon footprint minimization practices, as well as other implemented policies as an example of where HEIs should start on their road to a more sustainable institution.